ENERGY CONSERVATION RESEARCH OF LOW POWER SYNCHRONOUS ENGINES - Sharobiddinov Saydullo O’ktamjon’son; Rajapboyev Azimjon Nosirjon’s son (TADQIQOTLAR.UZ, 2024)
Annotatsiya: The energy efficiency of powerful synchronous motors is a multidimensional domain encompassing intricate technical considerations, engineering innovations, and industrial applications. Through the integration of advanced control systems, material science breakthroughs, thermal management strategies, and comparative analyses, the ongoing pursuit of enhanced energy efficiency in synchronous motors continues to drive progress and innovation in industrial power systems.